Influence of Motivation and Communication on Performance Teacher UPT. 1 Time SMPN - Nuning Nurna Dewi (Enrichment : Journal of Management, 2021)
Human resources in each school organization consist of several levels of position from the top (school principal) to the lowest (employees or workers). Therefore, with this position level, good communication is needed between superiors and subordinates, subordinates and superiors or fellow colleagues. Communication is quite important in a company system. Poor communication causes difficulties in collaboration between co-workers. However, we need to realize that communicating well without offending others is not an easy thing. This is because the quality of the available resources, skills, talents and abilities is generally heterogeneous. Good communication between superiors and subordinates or between co-workers, indirectly increasing productivity is not an easy job, because it is not only influenced by communication factors but also my own individual abilities. Because every individual has different backgrounds, experiences, expectations, emotions, and ambitions.